Conditional cash transfers programs and enforcement of compulsory education laws: The case of Asignacion Universal por Hijo in Argentina - Edo, María (2015)
Argentina has traditionally stood out in terms of educational outcomes among its Latin American counterparts. Schooling among older children, however, still shows room for improvement especially among the more vulnerable. Fortunately, the last decade witnessed a sizeable improvement in attendance rates for children aged 15 through 17. This could be related to the 2006 National Education Law that made uppersecondary education compulsory. In this paper, instead, we claim that the Asignación Universal por Hijo (AUH) a massive conditional cash transfer program implemented in 2009 in Argentina may be partly responsible for this improvement. Using a difference in difference model we estimate that the program accounts for a 3.9 percentage point increase in attendance rates among those eligible children aged 15 through 17.